Fabrikasi dan penganodan komposit metalurgi serbuk aluminium-magnesium diperkuat gentian pendek alumina saffil - Kamrosni, Abdul Razak
Anodising process on powder metallurgy aluminium-magnesium composites reinforced with short fibre alumina SaffilTM has been studied. PM Al-Mg composites were fabricated using PM route with Mg powder as the alloying element and short fibre alumina SaffilTM as the reinforcements. Mg powder was added in the rate of 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 wt% and short fibre alumina SaffilTM 5, 10, 15, 20 and 25 wt% to study the effect of adding those elements in various compositions. Microstructure analysis, density and porosity test and hardness test was used to determine the optimum weight percent of Mg powder and short fibre alumina SaffilTM in the PM Al-Mg composites. Result showed that 2.0 wt% of Mg is the best composition according to the surface morphology of the PM Al-Mg alloy with the least porosity. Meanwhile, the density and hardness recorded the highest value with this composition, 2.3 g/cm3 and 37.1 HVN accordingly. The optimum composition for short fibre alumina SaffilTM is 10% according to the density of 2.25 g/cm3, hardness value of 48 HVN, and had the most homogenous fibre distribution compared to the other compositions. After that, PM Al-Mg composite samples were coated in sulphuric acid anodising process. The study focused on effect of the various anodising voltage (10V, 12V, 14V, 16V and 18V) in 15% sulphuric acid and various concentration of sulphuric acid (5%, 10%, 15%, 20% and 25%) on the growth of a good anodising coating film. The anodising process were done in the room temperature (+25oC) for 60 minutes. The increasing of the coating film mass were recorded every 10 minutes for each anodising parameters. Cross sectional morphology was used to analyse the anodising coating film thickness formed on the surface of PM Al-Mg composites. The increasing of anodising voltage and concentration of sulphuric acid resulted on the increasing of anodising coating film. From the result, the most suitable anodising voltage is 16V and 15% concentration of sulphuric acid according to the coating film formed is uniform, less of porosity and showed the best rate of coating film mass. The maximum hardness value was also shown by anodising with 16V voltage (63HVN) and 15% concentration of sulphuric acid (64 HVN). After the anodising process, PM Al-Mg composite samples were tested in electrochemical testing in 3.5% NaCl solution to study the effect of various parameters of anodising coating on corrosion resistance. Tafel analysis showed that the corrosion rate was decreased and corrosion resistance was increased after the anodising coating process on PM Al-Mg composites. The minimum corrosion rate and maximum corrosion resistance were recorded by anodising with 16V voltage and 15% concentration of sulphuric acid, same goes to the best parameters of anodising. A good anodising coating can decrease the corrosion rate and increase the corrosion resistance of PM Al-Mg composite samples.